“Little Guests” Transnational “Humanitarian Hospitality” and Children’s Lives in the Aftermath of the Second World War - McEvoy, Lorraine Mary (Trinity College Dublin. School of Histories & Humanities. Discipline of History, 2024)
In the dying days and immediate aftermath of the Second World War, thousands of children criss-crossed Europe for the purposes of rest and recuperation. This thesis examines the welcome of children in Britain and Ireland, with a particular focus on the reception of Dutch children in Britain and German children in Ireland. By doing so, it seeks to expand the analytical framework for understanding this phenomenon. It approaches a transnational, comparative and integrated history and seeks to contribute to the intersecting historiographies of humanitarianism, childhood and postwar Europe. This thesis argues that using the lens of hospitality sheds a unique light on the nature of these experiences. The first two chapters analyse the organisation of these schemes in Britain and Ireland from the perspective of governments, NGOs and the general public. In chapter three, this is followed by an analysis of how children were selected for these schemes, how foster-families were recruited and how families navigated their separation. Chapter four examines the experiences of “little guests”, through the lens of children’s power and how adults engage with their past experiences.
APPROVED
Keywords: humanitarianism; postwar Europe; transnational history; childhood